Modelling and monitoring the behaviour of predators and prey in the context of anthropogenic risk - Lepard, C (2022)
Predator-prey dynamics help shape the populations and behavioural interactions of wildlife at all trophic levels. Risk effects are animals’ behavioural responses to the risk of predation and their associated costs. Humans impose risk effects on both predators and prey, and it’s important to understand those effects when developing conservation strategies. Here I examine the behaviours of Uganda kob (Kobus kob thomasi) and African lions (Panthera leo), both living in carnivore-ungulate systems within human-dominated landscapes. By recording kobs’ flight distances relative to road networks and snare poaching activity, I find that kobs’ antipredator responses do not seem to be affected by proximity to roads or local snaring intensity. However, sexual differences in flight distance may suggest intraspecific competition influences kobs’ risk tolerance. I also develop a model of lions’ energy expenditure over space and time as a result of habitat covariates. The construction of behavioural decision-making models could allow researchers to identify how lions and other carnivores perceive anthropogenic risk, given enough data to distinguish risk effects from other variables influencing their decisions. The aim of this thesis is to better understand the extent to which humans influence the behaviours of predators and prey and how human activities influence other animals’ perceptions of risk in dynamic ways.